Arsitektur Masjid Pekojan Semarang Sebagai Akulturasi Budaya Gujarat, China, Melayu, Eropa Dan Jawa - Mhd. Abdul Hafiz Damanik (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The Pekojan Mosque in Semarang is an example of Islamic architecture that is rich in historical and cultural value. This article aims to analyze the architectural elements contained in this mosque, and how these elements reflect the cultural and spiritual identity of the local community. Through a qualitative descriptive approach, this study identifies the physical and non-physical elements that form the characteristics of the Pekojan Mosque.